Odds of Anxiety and Depression Symptoms in School-Aged Children From Official Language Minority Communities - Dupuis, Jérémie B.; Bourque, Jimmy; El Adlouni, Salah-Eddine (Frontiers in Public Health, 2021)
Objectives: The aim of this paper is to assess the odds of suffering from anxiety or depression symptoms based on the presence of certain determinants of health for youth living in the province of New Brunswick, Canada, and in two linguistically different Official Language Minority Communities (OLMCs) in the same province. Methods: With a sample of 22,329 students from grades 7 to 12 in the province of New-Brunswick, logistic regressions were performed to assess each determinant of health’s effect on symptoms of anxiety and depression. Results: Some social determinants, like family support, social support and food insecurity, were identified as important determinants of mental health status regardless of linguistic group membership or community membership, while other determinants, such as alcohol use, cannabis use and natural environment, were more prominent in one OLMC than the other. Discussion: Social psychology and public health theories are used in an attempt to explain the results. Limitations and recommendations are also brought forward.